Legal Protection and Regulation of Thrifting Clothing Businesses: An Analysis of The Legality of Business Permits in Magetan - Muhammad Daqvara Akbar; Diana Setiawati; Jaka Susila (Proceeding International Conference Restructuring and Transforming Law, 2026)
Clothing not only serves as a basic necessity but also becomes part of an individual's lifestyle and identity. Developments in fashion, globalization, and technological advances have driven the emergence of the thrifting trend, which is popular among the younger generation due to its affordable prices, unique designs, and vintage feel. In Magetan Regency, the thrifting clothing business is growing rapidly and becoming a promising economic opportunity. However, the practice of importing used clothing has a negative impact on the domestic textile industry and has the potential to reduce state revenues. Therefore, the government has banned the import of used clothing through various regulations. Nevertheless, thrifting activities are still permitted as long as the goods traded are sourced domestically and comply with applicable legal provisions. This study aims to analyze the legal aspects of the thrifting business in Magetan Regency, specifically regarding business licensing, distribution of used clothing, and legal sanctions for violations. The research method used is empirical law with a sociological juridical approach, through data collection techniques such as interviews, observation, and documentation. The results show that one business actor, the Merapithrifstore Thrifting Shop, has not met legal standards because it does not have a business license. Furthermore, the widespread practice of thrifting reflects a gap between legal norms and social reality. High market demand, weak law enforcement, and the government's persuasive approach are factors contributing to the persistence of this practice. Therefore, the effectiveness of regulation depends heavily on consistent law enforcement and increased public legal awareness.